2016
DOI: 10.1177/1533034616657976
|View full text |Cite
|
Sign up to set email alerts
|

Amarogentin Induces Apoptosis of Liver Cancer Cells via Upregulation of p53 and Downregulation of Human Telomerase Reverse Transcriptase in Mice

Abstract: Background and Objective: Amarogentin has been reported to have a preventive effect on liver cancer via inducing cancer cell apoptosis. We attempted to elucidate the roles of p53-associated apoptosis pathways in the chemopreventive mechanism of amarogentin. The findings of this study will facilitate the development of a novel supplementary strategy for the treatment of liver cancer. Materials and Methods: The purity of amarogentin was assessed by high-performance liquid chromatography. The inhibitory ratios of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It has been reported that p53 is one of the tumor suppressor proteins that induces tumor cell cycle arrest and regulates programmed apoptosis in cancer cells [27]. Studies have found that Amarogentin can promote the apoptosis of liver cancer cells by up-regulating p53 of cells [28]. Another research points out that the expression of p53 is abnormally up-regulated in human colon cancer cells, and the activation of p53 can induce apoptosis of cancer cells and reduce cell migration [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that p53 is one of the tumor suppressor proteins that induces tumor cell cycle arrest and regulates programmed apoptosis in cancer cells [27]. Studies have found that Amarogentin can promote the apoptosis of liver cancer cells by up-regulating p53 of cells [28]. Another research points out that the expression of p53 is abnormally up-regulated in human colon cancer cells, and the activation of p53 can induce apoptosis of cancer cells and reduce cell migration [29].…”
Section: Discussionmentioning
confidence: 99%
“…Amarogentin, an anticancer compound extracted from Swertia davidi Franch , has been reported to inhibit liver cancer, cervical cancer, gastric carcinoma, and skin carcinogenesis in vivo and in vitro [ 11 , 12 , 20 22 ]. Sur et al have confirmed that amarogentin significantly reduces the numbers of LCSCs in both the pre- and postinitiation stages of carcinogenesis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the cells were cultured at 37°C for 12, 24, and 48 h for subsequent experiments. For amarogentin (21018-84-8, PUSH Bio-Tec, China) treatment, the iRFA models of HepG2 and Huh7 cell lines were incubated in a 50°C water bath for 10 min before treatment with amarogentin (120 μ g/ml) for 24 h. The optimal effective dose of amarogentin for liver cancer cell lines was determined in our previous study [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 More recently, AG was found to induce the apoptosis of liver cancer cells by the upregulation of p53 and downregulation of human telomerase reverse transcriptase. 10 Thus, because the AG content directly reects the potential activity of the extract, the quality control of Gentianaceae through the quantitative analysis of AG has recently attracted much attention. Currently, quantitative analysis for AG has been reported using liquid chromatography-mass spectrometry (LC-MS), 11 high-performance liquid chromatography (HPLC), 11,12 ultra-performance LC-electrospray ionization/MS, 13 and capillary electrophoresis.…”
Section: Introductionmentioning
confidence: 99%